An automated and compartmented fluidic reactor device for multi-step sample-to-answer processes using magnetic particles12. Issue 3 (24th February 2017) - Hübner, J.; Heinzler, R.; Arlt, C.; Hohmann, S.; Brenner-Weiß, G.; Franzreb, M.
Abstract : A benchtop device that combines segmented flow with magnetic particle separation and active resuspension capabilities for biotechnological applications, e.g. biomolecule purification. Abstract : To close the gap to automated systems capable of handling magnetic particles in liquid compartments at a scale between lab-on-a-chip systems and large pipetting stations, a compact reactor device for sample volumes between 1 and 1000 μL has been developed and thoroughly characterized. The device combines segmented flow technology, magnetic particle handling, and UV/VIS detection to enable automated sample-to-answer processes. The dosing accuracy of 10, 50 and 100 μL sized compartments separated by ethyl acetate, n -decane, PDMS and air was evaluated. For flow rates between 5 and 100 μL s −1, the dosing deviation for most process conditions was below 10%. The dosing accuracy decreased with increasing density differences between the single-phases. Carry-over examinations between subsequent compartments separated by ethyl acetate or air revealed a direct correlation between cross-contamination and increasing particle concentration and flow rate. A permanent magnetic field array used to separate the particles was tested for five commercial magnetic particle types. The array was able to retain all particle types with a maximum loss of 0.045 ± 0.031% per separation. An alternating electromagnetic field was used to resuspend the particles inside their fluidic environment in a contactless manner through the capillary wall. Depending on their magnetic properties, all particle types were resuspendable in buffer of moderate ionic strength within 0.4 and 16 s. To conclude, an example of a sample-to-answer multi-stage process is presented. DNA from lysed human whole blood was automatically isolated and analyzed inside the device. In this way, DNA at a concentration of 12.4 ± 1.9 μg mL −1 could be isolated, which was comparable to manual isolation in microcentrifuge tubes (13.0 ± 1.6 μg mL −1 ). The equal integrity of the DNA purified using the reactor and manually was verified by PCR.